Care situations demanding moral courage: Content analysis of nurses' experiences. (May 2020) - Kleemola, Emmi; Leino-Kilpi, Helena; Numminen, Olivia
Background: Nurses encounter complex ethical dilemmas in everyday nursing care. It is important for nurses to have moral courage to act in these situations which threaten patients' safety or their good care. However, there is lack of research of moral courage. Purpose: This study describes nurses' experiences of care situations demanding moral courage and their actions in these situations. Method: A qualitative descriptive research design was applied. The data were collected with an open-ended question in the questionnaire used in validation of the Nurses' Moral Courage Scale. The sample consisted of 286 nurses from four different clinical fields in a major university hospital in Finland, providing a total of 611 answers. Data were analyzed using inductive content analysis. Ethical considerations: The study followed the commonly recognized principles of good scientific practice. The use of data was authorized by the developer of the instrument, the data collector, and the participating hospital. Ethical approval was obtained from the university ethics committee. Findings: Nurses acted morally courageously in most situations but sometimes they failed to do so. Although situations demanding moral courage varied, they could be categorized into seven main domains relating to colleagues, physicians, patients, relatives, nurses themselves, managers, and organizations. Nurses acted in the situations in different ways. The main acts in solving the situations were verbal communication or immediate action, such as interrupting of action. Conclusion: Care situations demanding moral courage focus on good and safe patient care and the patient's good is at the center of attention. The situations are mostly related to the activities of other healthcare professionals. Findings may be applied in developing ethical nursing care through basic and continuing nursing education. Research is needed on the moral courage of physicians and managers, as well as on patients' and their relatives' experiences of care situations demanding moral courage.